2018
DOI: 10.1038/s41598-018-27482-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two different dosages of levofloxacin in curing Helicobacter pylori infection: A Prospective, Single-Center, randomized clinical trial

Abstract: Bismuth + proton pump inhibitor (PPI) + amoxicillin + levofloxacin is one of the bismuth quadruple therapy regimens widely used for the eradication of H. pylori infection. The recommended dosage of levofloxacin is 500 mg once daily or 200 mg twice daily to eradicate H. pylori infection. The aim of the present open-label, randomized control trial was to compare the effectiveness, safety, and compliance of different dosages of levofloxacin used to cure Helicobacter pylori infection. Eligible patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The results showed the superiority of oral levofloxacin 200 mg twice daily to oral levofloxacin 500 mg once daily for the eradication of H. pylori infection. [ 23 ] Other studies have recommended 500 mg levofloxacin once daily for H. pylori infection eradication. [ 24 ] Qian et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed the superiority of oral levofloxacin 200 mg twice daily to oral levofloxacin 500 mg once daily for the eradication of H. pylori infection. [ 23 ] Other studies have recommended 500 mg levofloxacin once daily for H. pylori infection eradication. [ 24 ] Qian et al .…”
Section: Discussionmentioning
confidence: 99%
“…Once-daily 14-and 7-day levofloxacin dosing regimens (levofloxacin, clarithromycin, rabeprazole, and bismuth) have shown eradication rates of 94% and 84%, respectively [77]. Gan et al compared the efficacy of different dosages of levofloxacin for the eradication of H. pylori [78]. The eradication rates in the once-and twice-daily groups were 77.5% and 79.5% (ITT) and 82.9% and 86.4% (PP), respectively [78].…”
Section: Levofloxacin-based Therapymentioning
confidence: 99%
“…Gan et al compared the efficacy of different dosages of levofloxacin for the eradication of H. pylori [78]. The eradication rates in the once-and twice-daily groups were 77.5% and 79.5% (ITT) and 82.9% and 86.4% (PP), respectively [78]. There are no significant differences in the eradication or compliance rate.…”
Section: Levofloxacin-based Therapymentioning
confidence: 99%
“…37 In Iran, a 10day sequential regimen using levofloxacin was found to have a 78% A randomized controlled trial from China looked at different dosages of levofloxacin as part of a bismuth quadruple regimen and found that 200 mg dosing, which achieved eradication in 79% of cases, was non-inferior to 500 mg dosages where 77% were cured, which has obvious cost and potential side effect implications.…”
Section: Le Voflox Acin -Ba S Ed Ther Apymentioning
confidence: 99%
“…A randomized controlled trial from China looked at different dosages of levofloxacin as part of a bismuth quadruple regimen and found that 200 mg dosing, which achieved eradication in 79% of cases, was non-inferior to 500 mg dosages where 77% were cured, which has obvious cost and potential side effect implications. 37 In Iran, a 10day sequential regimen using levofloxacin was found to have a 78% success rate compared to an 83% cure rate for 14-day quadruple therapy. 38 Finally, two studies compared levofloxacin-based therapy to standard triple therapy.…”
Section: Le Voflox Acin -Ba S Ed Ther Apymentioning
confidence: 99%